Filsafat Nusantara Pascakiamat - Mahaswa, Rangga Kala; Prayuda, Gloria Bayu Nusa (Sanata Dharma University, 2025)
The development of Nusantara Philosophy (Filsafat Nusantara) is inextricably linked to the politics of knowledge (philosophy) in Indonesia. Hitherto, Nusantara Philosophy has remained anchored in historical romanticism concerning the trajectory of philosophical thought in Indonesia. On the other hand, the paucity of futurist philosophical models or end-of-world philosophical approaches (apocalypse/post-apocalypse) in Indonesia poses a distinct challenge to the advancement of Nusantara Philosophy, particularly when addressing its own future. At this juncture, Nusantara Philosophy remains incomplete with itself, ensnared in issues of glorification, romanticism, uncertainty, and ambiguity surrounding its disparate, undirected concepts. Accordingly, this article illuminates several problems within Nusantara Philosophy through the lenses of archipelagic philosophical studies and speculative realism, to further elucidate the philosophical projections of Nusantara Philosophy when interrogating the Apocalypse. Certain analyses of Nusantara Philosophy merely catalog local knowledge, employing an approach inseparable from the cosmological-archipelagic model, wherein seas, mountains, and island expanses are envisioned as metaphysical agents serving as mediating mediums. Similarly, Nusantara Philosophy frequently generates diverse forms of speculative ethics that invariably compel consideration of specific moral values and cultural norms. Rather than seeking to transcend the universal claims of Western philosophy regarding apocalyptic/post-apocalyptic concepts, Nusantara Philosophy tacitly harbors a Ratu Adil (Just King) perspective to explicate the hyperobject of the end times.